LITERATURE REVIEW OF THE INTERNET OF THINGS ON THE DRINKING WATER MANAGEMENT SYSTEM - I Kadek Krisna Angga Pamungkas (International Journal of Engineering and Emerging Technology, 2021)
Excessive use of water will result in reduced clean water resources. At present the standard for water use in Indonesia is 60 liters per day per population but in reality the current use of water is 144 liters per day per population so that it still exceeds the standard. This article reviews water supply and distribution systems and research related to managing water consumption for daily needs. This review covers the process of water production to distribution to the community and the use of technology in managing water resources. The benefits of using IoT in water management allow users to monitor and control of water consumption in real time. Real-time control is achieved through the use of microcontroler-based platform such as Arduino Uno, NodeMCU and Wemos. Data is made available through mobile device access or website.